Total laparoscopic pancreaticoduodenectomy in 26 patients: single surgeon experience - Bagree, Rajendra; Jalendra, Gaurav; Panwar, Pradeep; Shukla, Veena; Reddy, Hetish M. (International Surgery Journal, 2021)
Background: Total laparoscopic pancreaticoduodenectomy (TLPD) has become more feasible and preferred surgery for periampullary tumour. With the innovation of latest equipment and continuous learning curve, this has become more sophisticated and rampant, along the advantages of minimal invasive surgery. Methods: We analysed data of all the 26 patients who underwent TLPD from October 2015 to November 2019. Preoperative haematological, liver function test, tumour marker, MRCP, triphasic CT, scan with pancreatic protocol, endoscopic ultrasound guided fine needle aspiration or brush cytology done for confirmation of diagnosis, nodal status and operability. Meticulously selected patients with periampullary carcinoma of tumour size≤2.5 cm included. Demographic data, operative time, length of hospital stay, post-operative complication and pathological analyses of resected specimen (en bloc) observed. Results: TLPD for periampullary tumours attempted in twenty-six patients among them six converted to open surgery. Patients were of both genders and mean age was 45 (27-60, SD7.4) years. The mean operative time was 353 SD 28.77 (306-420) minutes. Postoperatively, there were few complications and mean length of hospital stay was 11 (9-13 days) days. The histopathology revealed maximum no. of cholangiocarcinoma with negative margins and positive nodes in all the patients. Conclusions: TLPD is feasible, safe and promising alternative to the standard open surgery with expert hands. This has benefits of short hospital stay, less blood loss, cosmetic, early recovery with few complications. Short-term surgical outcomes are superior or comparable to open surgery.